Evaluating the final military phase of the Border War in south-eastern Angola 1987 -1988 - Szabo, Janet (Scientia Militaria - South African Journal of Military Studies, 2020)
The assessment of the final military phase of South Africa’s border war in southern Angola from 1987 to 1988 in terms of victory or defeat is not without controversy. The mobile engagements on the Lomba between the South Africans (in support of UNITA) and the Angolan armed forces (FAPLA), saw a clear victory for the SADF when assessed in terms of achievement of objectives, equipment captured and destroyed as well as enemy casualties. South Africa’s offensive manoeuvres on the Chambinga River - particularly regarding the Angolan 16th Brigade as more recent information indicates - were also successful in inflicting significant losses of men and equipment and damaging morale. However, once the SADF switched from mobile warfare – which allowed it to effectively engage the Angolans who had superior numbers – to positional warfare against larger numbers of Angolan and Cuban forces in well-prepared and defended positions at Tumpo opposite Cuito Cuanavale, the picture changed. Tumpo can thus be regarded as a stalemate. South Africa had achieved its objective of preventing UNITA’s annihilation and inflicted sufficient losses on FAPLA. But it had not managed to completely dislodge the Angolan and Cuban forces from the east bank of the Cuito River.